Conceptual design of heterogeneous azeotropic distillation process for ethanol dehydration using 1-butanol as entrainer - Paritta Prayoonyong (Maejo International Journal of Science and Technology, 2014)
The synthesis of a heterogeneous azeotropic distillation process for ethanol dehydration using 1-butanol as entrainer is presented. The residue curve map of the ethanol/water/1-butanol mixture is computationally generated using non-random twoliquid thermodynamic model. It is found that 1-butanol leads to a residue curve map topological structure different from that generated by typical entrainers used in ethanol dehydration. Synthesised by residue curve map analysis, the distillation flowsheet for ethanol dehydration by 1-butanol comprises a double-feed column integrated with an overhead decanter and a simple column. The double-feed column is used to recover water as the top product, whereas the simple column is used for recovering ethanol and 1-butanol. The separation feasibility and the economically near-optimal designs of distillation columns in the flowsheet are evaluated and identified by using the boundary value design method. The distillation flowsheet using 1-butanol is compared with the conventional process using benzene as entrainer. Based on their total annualised costs, the ethanol dehydration process using 1-butanol is less economically attractive than the process using benzene. However, 1-butanol is less toxic than benzene.